A Regime-Based Effect of Fiscal Policy : Evidence from an Emerging Economy - Bouzid, Bechir N. (World Bank, Washington, DC, 2017)
In recent years, few authors have attempted to address the question of whether the state of the economy influences the impact of fiscal policy on the economy. Key findings have often indicated that expansionary fiscal intervention tends to be more effective when the economy is in a downturn. This favorable impact is more pronounced with an increase in government spending as opposed to a tax reduction. Despite several empirical attempts, the findings on the state-dependent nonlinear relationship of fiscal policy and output growth are often limited to developed economies. Building on the current research trend of using the threshold vector autoregression methodology, this paper bridges this gap and extends the empirical body to estimate the nonlinear relationship for an emerging economy, Tunisia. The paper provides empirical evidence that fiscal policy has a different impact on economic activity depending on the business cycle, the instrument of the fiscal policy used, and the intensity of the shock. The paper argues that in a downturn phase, government spending should be privileged particularly in the short run, with a gradual increase in the tax base to reduce the risk of worsening the budget deficit. Further, the monetary authority should be less inclined to raise its policy rate in the early stage of the recessionary period, as this intervention could have an adverse impact on economic growth. In the expansion phase, a tax cut intervention appears on the contrary to have a stronger positive impact on economic activity, especially in the short run, as the monetary authority is expected to introduce gradual policy hikes more rapidly to control for the inflationary expectations.